The Impact of Covid-19 on Tourist Consumption Behaviour : A Perspective Article - Chebli, Amina; Said, Foued Ben (Journal of Tourism Management Research, 2020)
The study aims to explore the impact of the coronavirus pandemic (Covid-19) on tourist behaviour and identifies intentions to change tourist behaviour that will emerge as a result of this pandemic. In the absence of a similar previous study, this study is designed to be a polite study. 308 travellers, selected on a non-probabilistic basis, participated in this pilot research. The data collected were subjected to Chi-square test of goodness of fit test statistical analysis and content analysis. The results indicate that the current Covid-19 pandemic is expected to have an impact on traveler behavior intentions, in terms of personal safety, economic expenditure, conviction and attitude. Finally, key findings and practical implications of this study are described for the management of this crisis, based on the results and limitations of this research, future research directions are presented. To the best of our knowledge, this paper provides the first exploratory analysis of the consequences that the Covid-19 health crisis is expected to have on travel behaviour.